Human Development: Beyond the Human Development Index. - Ranis, G; Stewart, F; Samman, E (2006)
The well-known Human Development Index (HDI) encompasses only three rather basic aspects of human welfare. This paper aims to go beyond this, by identifying 11 categories of human development. We next propose plausible candidates as indicators of these categories. We then estimate correlations among the indicators within each category, discarding those that are highly correlated with others. This left 39 indicators to encompass the categories. Of these, eight indicators are highly correlated with the HDI and may therefore be represented by it. But 31 are not highly correlated, suggesting that a full assessment of human development requires a much broader set of indicators than the HDI alone. Following the same procedure, we find that under-five mortality rates perform equally as well as the HDI, and income per capita is less representative of other dimensions of human development. The HDI (and the other two broad indicators) are shown to be worse indicators of the extended categories of human development for OECD countries than for developing countries.